EFFECT OF INLATION ON NOMINAL AND REAL STOCK RETURNS: A BEHAVIORAL VIEW - KUDRYAVTSEV , Andrey; LEVAV , Eyal; SHAHRABANI , Shosh (Journal of Advanced Studies in Finance; Vol 5 No 1 (2014): JASF Volume V, Issue 1(9), Summer, 2014, 2014)
The main goal of this study is to shed light on different aspects of the correlation between stock market returns and inflation. Using historical monthly rates of inflation calculated by the Israel Central Bureau of Statistics and historical monthly returns on six leading stock indices of the Tel Aviv Stock Exchange, we document that nominal stock index returns do not compensate investors either for contemporaneous inflation (inflation rate registered during the same month as the index return) or for previous month's inflation (inflation rate officially announced during the month when the index return is observed). In addition, the results indicate that real stock index returns (calculated by deducting the rate of inflation from the nominal return rate) are negatively correlated with contemporaneous inflation rates. We suggest a behavioral explanation for these findings based on the assumption that investors perceive inflation itself as bad news and subsequently downwardly update their estimates of (at least real) expected cash-flows from holding the stocks and/or upwardly update the expected risk levels of the stocks.